Brand turnaround how brands gone bad returned to glory and the seven game changers that made the difference - Post, Karen (New York McGraw-Hill, 2012)
How did Toyota, Tylenol, and Goldman Sachs bounce back from the brink of destruction? This book reveals the answers and provides valuable lessons for anyone tasked with reviving a brand.
Ford, Xerox, and Domino's. Each of these high-profile brands faced a widely publicized meltdown that threatened to put them out of business- and each one is going strong today. Why? They took charge with conviction, creativity, and smarts. This book examines these and other brands, big and small, to prove that with the right plan and leadership any brand can recover. Karen Post, a leading expert on branding, provides practical insight and methods you can use to transform your brand when it seems the world is crashing down around it. Post has researched the brand-recovery strategies from a diverse mix of more than 75 brands- from Ford, JetBlue, and the Red Cross to Robert Downey, Jr., Arianna Huffington, Michael Vick, and Martha Stewart. She details the brand-damaging events and examines the steps each brand took to return to glory, then applies the best practices into a powerful, seven-step process you can use to keep your brand moving forward through any storm. -- Book Jacket.
It's a brand new game -- Mission possible : brands can turn around -- The warning is on the label and the clock is ticking -- Chains hold you hostage : change can set you free -- Seven game changers that made the difference -- Game changer 1: Take responsibility -- Game changer 2: Never give up -- Game changer 3: Lead strong -- Game changer 4: Stay relevant -- Game changer 5: Keep improving -- Game changer 6: Build equity -- Game changer 7: Own your distinction.
Includes bibliographical references and index.
CSSP-8658 gift of The Asia Foundation and MoneyGram Foundation.
Keywords: Brand name products; Branding (Marketing); Technological innovations -- Management